Midsommar [videorecording (DVD)] - Aster, Ari; Pugh, Florence, 1996-; Reynor, Jack, 1992-; Harper, William Jackson, 1980- (Lionsgate, 2019)
A young woman reluctantly joins her boyfriend on a summer trip to a Swedish festival where things quickly go awry.